MYŚL POLITYCZNO-PRAWNA I DZIAŁALNOŚĆ POLSKIEGO STRONNICTWA LUDOWEGO ZIEMI WILEŃSKIEJ W OKRESIE DWUDZIESTOLECIA MIĘDZYWOJENNEGO - Dąbrowski, Przemysław (Zeszyty Prawnicze, 2016)
POLITICAL – LEGAL THOUGHT AND ACTIVITY OF POLISH PEOPLE’S PARTY VILNIUS LAND IN PERIOD OF INTERWAR TWO DECADES Summary Polish people’s movement on lands of former Grand Duchy of Lithuania begin forming on this area after first world war. It did not present construction from start almost homogeneous, about one program or compact organizational structure. On Vilnius’s earth acted in years 1918-1939 different groups and institutions at the nature people’s, like: People’s Advices Councils – by found Vilnius department Company of Borderland Guard, Polish People’s Association “Odrodzenie” – to Polish People’s Party “Wyzwolenie” transformed next (then in June 1922 year, organization has accepted name of Polish People’s Party “Wyzwolenie” Vilnius and Novgorod Land), Borderland Peasant Party, Independent Peasant Party or Polish Party of People’s Vilnius Land. Party has played significant and in period of functioning prominent role only Middle Lithuania. Activity of group has been limited after 1922 year, by the reason of its secession of foremost representative surely. However, meanings not crossing out, that has played this party on Vilnius Land, it belongs to ascertain, that it presented certain counterweight for other political parties many times, mainly leftist, defending same interest of Vilnius Land and take care of its fate. It concerned program of party on principle of federation solution of attitude relation Polish – Lithuanian, but next autonomy. It appeal about decentralization of state also, and as most fast conducting of rural reform and correction of condition of vital urban population, through braving abuse.